2014
DOI: 10.3174/ajnr.a4070
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal White Matter Integrity in Chronic Users of Codeine-Containing Cough Syrups: A Tract-Based Spatial Statistics Study

Abstract: BACKGROUND AND PURPOSE:Codeine-containing cough syrups have become one of the most popular drugs of abuse in young people in the world. Chronic codeine-containing cough syrup abuse is related to impairments in a broad range of cognitive functions. However, the potential brain white matter impairment caused by chronic codeine-containing cough syrup abuse has not been reported previously. Our aim was to investigate abnormalities in the microstructure of brain white matter in chronic users of codeine-containing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…2 Nonmedical use of cough (NUCS) had become one of the commonly used abusive substances among adolescents in Western countries 3,4 and some Asian countries. 59 In China, cough syrup is commonly considered as addictive, 10–12 given the 2 dominating types of cough syrups: 1 is codeine containing, the other is Chinese herbal cough syrup that contains components extracted from pericarpium papaveris, that is, poppy shell. 13 There are very limited studies on the NUCS in China.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Nonmedical use of cough (NUCS) had become one of the commonly used abusive substances among adolescents in Western countries 3,4 and some Asian countries. 59 In China, cough syrup is commonly considered as addictive, 10–12 given the 2 dominating types of cough syrups: 1 is codeine containing, the other is Chinese herbal cough syrup that contains components extracted from pericarpium papaveris, that is, poppy shell. 13 There are very limited studies on the NUCS in China.…”
Section: Introductionmentioning
confidence: 99%
“…9,1720 Studies suggested that NUCS might cause or co-exist with illicit drug use, and NUCS users are more inclined to become polydrug addicts. 19,20 In addition, NUCS is also associated with damages to white matter of brain, 9 the volume loss and aberrant functional organization in ventral medial prefrontal cortex, 21 folate deficiency, 17,22 and neural tube defects in fetus. 23 Furthermore, the damages to brain in NUCS users may be linked to higher impulsivity, 9,21 which in turn could lead to more serious drug-seeking behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The withdrawal symptoms from codeine are lighter than those of other opioids such as morphine and heroin. Codeine-containing cough syrups contain a combination of codeine, a sympathomimetic, and an antihistamine, all of which have central nervous system action (Qiu et al, 2015(Qiu et al, , 2016.…”
Section: Proton Magnetic Resonance Spectroscopy Is a Noninvasive Neuro-mentioning
confidence: 99%
“…Opioid dependence, which is characterized by extremely unpleasant physical and emotional feelings after drug use is terminated (Zhu, Wienecke, Nachtrab, & Chen, 2016), is a highly prevalent addictive disorder associated with comorbid medical and psychiatric problems (Rodriguez-Cintas et al, 2016). Most previous studies of drug addiction's effect on brain systems have focused on illicit drugs, such as heroin, cocaine, cannabis (Greenwald, Woodcock, Khatib, & Stanley, 2015;Paydary et al, 2016;Rodriguez-Cintas et al, 2016), as opposed to legal opiates (e.g., codeine, morphine, and opium) (Kim, Ham, Hong, Moon, & Im, 2016;Qiu, Su, Lv, & Jiang, 2015;Schuckit, 2016). Long-term use of prescription opioid exposes patients to risk of developing addictive side effects, such as rewarding and withdrawal symptoms (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%